AMIR TEMUR’S CONSTRUCTIONS AND THE SPIRITUAL IDEAS ADVANCED IN IT - Ahmedov Azimjon; Yusufjonova Malohatoy (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: In this article, the content of the work "Temur's rules" written by Amir Temur, the ideas put forward in the game, such as humanity, honesty, moral norms, the categories that form the basis of the state in the play and the views of other scholars on “Temur’s rules” detailed information is given